Temperature regulator for containers with working substance in high-frequency metal vapor active media; Journal of Physics: Conference Series; Vol. 1327 : Innovations in Non-Destructive Testing (SibTest 2019) - Bukreev E. G.; Kozhemyak O. A. Olesya Anatolievna; Musorov I. S. Ilia Sergeevich; Ogorodnikov D. N. Dmitry Nikolaevich; Drobchik V. V. (2019, 2019)
Title screen